Appendicular lean mass index using dual-energy X-ray absorptiometry (DEXA) in professional football: a pilot study of a new method for improved inter-operator reproducibility and analysis of pelvi-trochanteric muscles - Evrard, C.; Blaess, J.; Goetsch, T.; Fellous, E.; Pietra, F.; Meyer, A.; Giannini, M.; Geny, B. (Sports, 2025)
Background: Body composition assessment is important in professional football as a measure of overall adaptation of the athlete to the training demand and calorie intake. However, it is operator-dependent, relying on subject positioning and the focus angle of the X-rays. In addition, the usual appendicular lean mass index (ALMI) does not include the pelvitrochanteric muscles, which are often implicated in athlete injuries.